Penggunaan Digital Touch Panel terhadap Survei Kepuasan Pelayanan di Kantor Desa Dauh Puri Kauh Denpasar - Made Dika Nugraha; I Putu Yudi Prabhadika; Ida Ayu Rosa Dewinta (Universitas Warmadewa, 2023)
Community service at the Dauh Puri Kauh Village Office is a form of campus concern for the environment, both for the general public, government and village officials who oversee the Denpasar city area, especially the West Denpasar sub-district. They complained about the lack of understanding of most employees about application of digital technology, especially the use of digital service satisfaction survey tools that do not yet exist in the West Denpasar government area because what employees often use is only a piece of paper to survey community satisfaction in the form of a questionnaire answer format which is archived and input manually to computer databases. Considering that currently the need for good, fast and accurate services is urgently needed by the people of the Dauh Puri Kauh area and that information disclosure and services are digital, especially in the Denpasar city area after the Covid-19 spike has decreased. This service will involve the village head and employees of the Dauh Puri Kauh village office. The results of the service are expected to help capable partners who are expected to be able to understand and continue the application of the tool and in the future, the system can be developed for the advancement of digital technology in the Denpasar city area.